2016
DOI: 10.1080/0284186x.2016.1253861
|View full text |Cite
|
Sign up to set email alerts
|

Methodological, biological and clinical aspects of circulating free DNA in metastatic colorectal cancer

Abstract: Background: Circulating DNA can be used to measure the total cell-free DNA (cfDNA) and for detection and quantification of tumor-specific genetic alterations in the peripheral blood, and the broad clinical potential of circulating DNA has attracted increasing focus over the past decade. Concentrations of circulating DNA are high in metastatic colorectal cancer (CRC), and the total levels of cfDNA have been reported to hold strong prognostic value. Colorectal tumors are characterized by a high frequency of well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 92 publications
(161 reference statements)
1
30
0
Order By: Relevance
“…Another study showed a strong association between ctDNA positivity and recurrence‐free survival (RFS), and overall survival (OS) in patients with CRC irrespective of tumor stage, study size, tumor markers, detection methods, and sample type . A meta‐analysis of 1076 patients with mCRC treated with chemotherapy confirmed that baseline total cfDNA levels correlate with OS . The utility of ctDNA and cfDNA as a prognostic parameter and alternative modality for mutation detection before treatment in metastatic CRC (mCRC) was demonstrated in the randomized CORRECT phase III trial .…”
Section: Clinical Relevance Of Ctdna For Advanced Crcmentioning
confidence: 99%
See 4 more Smart Citations
“…Another study showed a strong association between ctDNA positivity and recurrence‐free survival (RFS), and overall survival (OS) in patients with CRC irrespective of tumor stage, study size, tumor markers, detection methods, and sample type . A meta‐analysis of 1076 patients with mCRC treated with chemotherapy confirmed that baseline total cfDNA levels correlate with OS . The utility of ctDNA and cfDNA as a prognostic parameter and alternative modality for mutation detection before treatment in metastatic CRC (mCRC) was demonstrated in the randomized CORRECT phase III trial .…”
Section: Clinical Relevance Of Ctdna For Advanced Crcmentioning
confidence: 99%
“…For example, liquid biopsies have been successfully applied to identify mechanisms of resistance for epidermal growth factor (EGFR) inhibitor in mCRC patients . Significant proportions of CRC harbor mutations in KRAS , BRAF , or NRAS that could cause resistance to an EGFR inhibitor, and these hotspot mutations are candidates for mutations detectable in plasma . Previous reports showed that patients with RAS wild‐type CRC in tissue, and plasma that is positive for KRAS and BRAF mutations can be resistant to the EGFR inhibitor .…”
Section: Clinical Relevance Of Ctdna For Advanced Crcmentioning
confidence: 99%
See 3 more Smart Citations